Helminth-modified pulmonary response protects mice from allergen-induced airway hyper-responsiveness. - FALLON, PADRAIC (The American Association of Immunologists, 2006)
It has been shown that the presence of certain helminth infections in humans, including schistosomes, may reduce the propensity to develop allergies in infected populations. Using a mouse model of schistosome worm vs worm + egg infection, our objective was to dissect the mechanisms underlying the inverse relationship between helminth infections and allergies. We have demonstrated that conventional Schistosoma mansoni egg-laying male and female worm infection of mice exacerbates airway hyperresponsiveness. In contrast, mice infected with only schistosome male worms, precluding egg production, were protected from OVA-induced airway hyperresponsiveness. Worm-infected mice developed a novel modified type 2 cytokine response in the lungs, with elevated allergen-specific IL-4 and IL-13 but reduced IL-5, and increased IL-10. Although schistosome worm-only infection is a laboratory model, these data illustrate the complexity of schistosome modulation of host immunity by the worm vs egg stages of this helminth, with the potential of infections to aggravate or suppress allergic pulmonary inflammation. Thus, infection of mice with a human parasitic worm can result in reduced airway inflammation in response to a model allergen.
PUBLISHED
Keywords: Clinical Medicine